A noninvasive system‐level model order reduction scheme for flexible multibody simulation. (31st March 2020) - Naets, Frank; Devos, Thijs; Humer, Alexander; Gerstmayr, Johannes
Abstract: This paper presents a novel system‐level model order reduction scheme for flexible multibody simulation, namely the system‐level affine projection (SLAP). Contrary to existing system‐level model order reduction approaches for multibody systems simulation, this methodology allows to obtain a constant reduced order basis which can be obtained in a noninvasive fashion with respect to the original flexible multibody model. It is shown that this scheme enables an automatic joint constraint elimination which can be obtained at low computational cost through exploitation of the component level modes typically employed in flexible multibody simulation. The equations of motion are derived such that the computational cost of the resulting SLAP model is independent of the original model size. This approach results in a set of ordinary differential equations with a constant mass matrix and nonlinear internal forces. This structure makes the resulting model suitable for a range of estimation, control, and design applications. The proposed approach is validated numerically on a flexible four‐bar mechanism and shows good accuracy for a very low‐order SLAP model.